Legal Certainty in The Fulfillment of Creditors’ Rights in Debt Disputes Concluding in Bankruptcy: Kepastian Pemenuhan Hak Kreditor dalam Sengketa Hutang Piutang yang Berakhir dengan Kepailitan - Fidda Nazli Azzahra; Andriyanto Adhi Nugroho (Academia Open, 2025)
General Background: Rapid growth in business activities in Indonesia has intensified debt–credit relations, increasing the frequency of disputes that culminate in bankruptcy proceedings. Specific Background: Although Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations (PKPU) provides procedural safeguards, practical implementation often raises concerns regarding creditor protection, as illustrated by Case No. 33/Pdt.Sus-PKPU/2020/PN Niaga Jakarta Pusat and subsequent Supreme Court decisions. Knowledge Gap: Prior studies have insufficiently examined how normative bankruptcy mechanisms operate in practice to protect creditors amid disparities among creditor classes. Aims: This study aims to analyze the forms of legal protection afforded to creditors and identify obstacles faced in realizing their rights within bankruptcy proceedings. Results: The findings show that creditor protection is formally structured through PKPU procedures, claim verification, creditor meetings, voting, homologation, and curator supervision; however, effectiveness is undermined by unequal bargaining positions, debtor non-compliance with peace agreements, and weak oversight. Novelty: This study integrates normative analysis with a detailed case study to reveal gaps between statutory design and judicial practice in creditor protection. Implications: The results suggest the need for regulatory refinement, stronger judicial supervision, and improved professional standards to ensure a fair, transparent, and effective bankruptcy system that genuinely safeguards creditors’ rights. Highlights: Normative Framework vs. Practice: Formal bankruptcy procedures exist, yet their implementation often fails to ensure equal and effective creditor protection. Creditor Inequality: Differences between secured and unsecured creditors create structural imbalances in the fulfillment of claims. Enforcement Challenges: Debtor non-compliance and weak supervision reduce the effectiveness of peace agreements and legal remedies. Keywords: Bankruptcy, Creditor Protection, PKPU, Legal Certainty, Commercial Court